Nagwa uses cookies to ensure you get the best experience on our website. Learn more about our Privacy Policy.

Start Practicing

Worksheet: Differentiation of the General Exponential Function

Q1:

If 𝑦 = βˆ’ 3 Γ— 2 π‘₯ , determine d d 𝑦 π‘₯ .

  • A βˆ’ 6 2 l n π‘₯
  • B βˆ’ 3 Γ— 2 2 π‘₯ π‘₯ l n
  • C βˆ’ 6 2 l n
  • D βˆ’ 3 Γ— 2 2 π‘₯ l n

Q2:

Find d d 𝑦 π‘₯ if 𝑦 = 4 ( 9 π‘₯ βˆ’ 4 π‘₯ + 8 ) 2 .

  • A 4 4 l n ( 9 π‘₯ βˆ’ 4 π‘₯ + 8 ) 2
  • B 4 4 ( 9 π‘₯ βˆ’ 4 π‘₯ + 8 ) 2 l n
  • C 8 ( 9 π‘₯ βˆ’ 2 ) 4 l n ( 9 π‘₯ βˆ’ 4 π‘₯ + 8 ) 2
  • D 2 ( 9 π‘₯ βˆ’ 2 ) 4 4 ( 9 π‘₯ βˆ’ 4 π‘₯ + 8 ) 2 l n

Q3:

Find d d 𝑦 π‘₯ if 𝑦 = 8 ( 3 π‘₯ βˆ’ 5 π‘₯ + 8 ) 2 .

  • A 8 8 l n ( 3 π‘₯ βˆ’ 5 π‘₯ + 8 ) 2
  • B 8 8 ( 3 π‘₯ βˆ’ 5 π‘₯ + 8 ) 2 l n
  • C 8 ( 6 π‘₯ βˆ’ 5 ) 8 l n ( 3 π‘₯ βˆ’ 5 π‘₯ + 8 ) 2
  • D ( 6 π‘₯ βˆ’ 5 ) 8 8 ( 3 π‘₯ βˆ’ 5 π‘₯ + 8 ) 2 l n

Q4:

Find the derivative of the function 𝑦 = 2 5 7 π‘₯ .

  • A 𝑦 β€² = 2 5 7 β‹… 2 l n l n l n 5 7 π‘₯
  • B 𝑦 β€² = 7 β‹… 2 β‹… 5 β‹… 7 l n 5 7 π‘₯ 7 π‘₯ π‘₯
  • C 𝑦 β€² = 5 β‹… 2 β‹… 2 7 5 π‘₯ 7 π‘₯ l n
  • D 𝑦 β€² = 2 5 7 β‹… 2 β‹… 5 β‹… 7 l n l n l n 5 7 π‘₯ 7 π‘₯ π‘₯
  • E 𝑦 β€² = 2 β‹… 2 5 7 π‘₯ l n

Q5:

Find the derivative of the function 𝑦 = 3 2 7 π‘₯ .

  • A 𝑦 β€² = 2 3 7 β‹… 3 l n l n l n 2 7 π‘₯
  • B 𝑦 β€² = 7 β‹… 3 β‹… 2 β‹… 7 l n 2 7 π‘₯ 7 π‘₯ π‘₯
  • C 𝑦 β€² = 2 β‹… 3 β‹… 3 7 2 π‘₯ 7 π‘₯ l n
  • D 𝑦 β€² = 2 3 7 β‹… 3 β‹… 2 β‹… 7 l n l n l n 2 7 π‘₯ 7 π‘₯ π‘₯
  • E 𝑦 β€² = 3 β‹… 3 2 7 π‘₯ l n

Q6:

Determine the derivative of π‘Ÿ ( 𝑑 ) = 8 6 √ 𝑑 .

  • A π‘Ÿ β€² ( 𝑑 ) = 8 8 6 √ 𝑑 l n
  • B π‘Ÿ β€² ( 𝑑 ) = 6 Γ— 8 √ 𝑑 6 √ 𝑑 βˆ’ 1
  • C π‘Ÿ β€² ( 𝑑 ) = 8 8 2 √ 𝑑 6 √ 𝑑 l n
  • D π‘Ÿ β€² ( 𝑑 ) = 3 Γ— 8 8 √ 𝑑 6 √ 𝑑 l n
  • E π‘Ÿ β€² ( 𝑑 ) = 3 6 Γ— 8 6 √ 𝑑

Q7:

Determine the derivative of π‘Ÿ ( 𝑑 ) = 9 7 √ 𝑑 .

  • A π‘Ÿ β€² ( 𝑑 ) = 9 9 7 √ 𝑑 l n
  • B π‘Ÿ β€² ( 𝑑 ) = 7 Γ— 9 √ 𝑑 7 √ 𝑑 βˆ’ 1
  • C π‘Ÿ β€² ( 𝑑 ) = 9 9 2 √ 𝑑 7 √ 𝑑 l n
  • D π‘Ÿ β€² ( 𝑑 ) = 7 Γ— 9 9 2 √ 𝑑 7 √ 𝑑 l n
  • E π‘Ÿ β€² ( 𝑑 ) = 4 9 Γ— 9 7 √ 𝑑

Q8:

Find the derivative of the function 𝑔 ( π‘₯ ) = ( 2 π‘Ÿ π‘Ž + 𝑛 ) π‘Ÿ π‘₯ 𝑝 , where π‘Ž , 𝑝 , π‘Ÿ , and 𝑛 are constants.

  • A 𝑔 β€² ( π‘₯ ) = 2 π‘Ÿ 𝑝 ( 2 π‘Ÿ π‘Ž + 𝑛 ) π‘Ž π‘Ÿ π‘₯ 𝑝 βˆ’ 1 π‘Ÿ π‘₯
  • B 𝑔 β€² ( π‘₯ ) = 2 π‘Ÿ 𝑝 ( π‘Ž ) ( 2 π‘Ÿ π‘Ž + 𝑛 ) π‘Ž l n π‘Ÿ π‘₯ 𝑝 βˆ’ 1 π‘Ÿ π‘₯
  • C 𝑔 β€² ( π‘₯ ) = 2 π‘Ÿ 𝑝 ( π‘Ž ) ( 2 π‘Ÿ π‘Ž + 𝑛 ) 2 π‘Ÿ π‘₯ 𝑝 l n
  • D 𝑔 β€² ( π‘₯ ) = 2 π‘Ÿ 𝑝 ( π‘Ž ) ( 2 π‘Ÿ π‘Ž + 𝑛 ) π‘Ž 2 π‘Ÿ π‘₯ 𝑝 βˆ’ 1 π‘Ÿ π‘₯ l n
  • E 𝑔 β€² ( π‘₯ ) = 2 π‘Ÿ 𝑝 ( 2 π‘Ÿ π‘Ž + 𝑛 ) 2 π‘Ÿ π‘₯ 𝑝 βˆ’ 1

Q9:

Determine the derivative of 𝑓 ( 𝑑 ) = 6 𝑑 7 .

  • A 𝑓 β€² ( 𝑑 ) = 6 6 𝑑 7 l n
  • B 𝑓 β€² ( 𝑑 ) = 6 𝑑 6 𝑑 βˆ’ 1 7 7 l n
  • C 𝑓 β€² ( 𝑑 ) = 6 𝑑 6 𝑑 6 7 l n
  • D 𝑓 β€² ( 𝑑 ) = 7 β‹… 6 𝑑 6 𝑑 6 7 l n
  • E 𝑓 β€² ( 𝑑 ) = 7 β‹… 6 𝑑 𝑑 6 7

Q10:

Find the derivative of the function 𝐺 ( π‘₯ ) = 2 𝐢 π‘₯ .

  • A 𝐺 β€² ( π‘₯ ) = βˆ’ 𝐢 2 π‘₯ 𝐢 π‘₯ 2
  • B 𝐺 β€² ( π‘₯ ) = 𝐢 ( 2 ) 2 π‘₯ l n 𝐢 π‘₯ 2
  • C 𝐺 β€² ( π‘₯ ) = βˆ’ 𝐢 ( 2 ) 2 π‘₯ l n 𝐢 π‘₯
  • D 𝐺 β€² ( π‘₯ ) = βˆ’ 𝐢 ( 2 ) 2 π‘₯ l n 𝐢 π‘₯ 2
  • E 𝐺 β€² ( π‘₯ ) = 𝐢 ( 2 ) 2 π‘₯ l n 𝐢 π‘₯

Q11:

Find d d 𝑦 π‘₯ if 𝑦 = 4 ο€Ή 8 π‘₯ βˆ’ 4  8 π‘₯ 8 4 .

  • A 4  ο€Ή 8 π‘₯ βˆ’ 4  4 + 6 4 π‘₯  8 π‘₯ 8 7 4 l n
  • B 4  3 2 π‘₯ ο€Ή 8 π‘₯ βˆ’ 4  + 6 4 π‘₯  8 π‘₯ 3 8 7 4
  • C 4  3 2 ο€Ή 8 π‘₯ βˆ’ 4  4 + 6 4 π‘₯  8 π‘₯ 8 7 4 l n
  • D 4  3 2 π‘₯ ο€Ή 8 π‘₯ βˆ’ 4  4 + 6 4 π‘₯  8 π‘₯ 3 8 7 4 l n
  • E 3 2 π‘₯ ο€Ή 8 π‘₯ βˆ’ 4  4 + 6 4 π‘₯ 3 8 7 l n

Q12:

Find the first derivative of the function 𝑦 = ο€Ή 7  βˆ’ 9 π‘₯ βˆ’ 8 βˆ’ 2 .

  • A βˆ’ 2 ο€Ή 7  βˆ’ 9 π‘₯ βˆ’ 8 βˆ’ 3
  • B ο€Ή 7  7 1 8 π‘₯ + 1 6 l n
  • C βˆ’ 2 ο€Ή 7  l n βˆ’ 9 π‘₯ βˆ’ 8
  • D 1 8 ο€Ή 7  7 1 8 π‘₯ + 1 6 l n

Q13:

Given that 𝑦 = βˆ’ 9 5 π‘₯ 2 𝑒 s i n 2 π‘₯ , find d d 𝑦 π‘₯ .

  • A βˆ’ 9 2 𝑒 ( βˆ’ 2 5 π‘₯ + 5 π‘₯ ) βˆ’ 2 π‘₯ s i n c o s
  • B 9 2 𝑒 ( 2 5 π‘₯ + 5 5 π‘₯ ) βˆ’ 2 π‘₯ s i n c o s
  • C 9 2 𝑒 ( 2 5 π‘₯ + 5 π‘₯ ) βˆ’ 2 π‘₯ s i n c o s
  • D βˆ’ 9 2 𝑒 ( βˆ’ 2 5 π‘₯ + 5 5 π‘₯ ) βˆ’ 2 π‘₯ s i n c o s

Q14:

Given 𝑦 = 9 ο€Ί √ π‘₯ + 6 π‘₯  π‘₯ 4 , find d d 𝑦 π‘₯ .

  • A 9 ο€Ώ 2 4 π‘₯ + 1 2 √ π‘₯  + ο€Ί √ π‘₯ + 6 π‘₯  9 π‘₯ 3 4 l n
  • B 9 ο€Ί √ π‘₯ + 6 π‘₯  9 + 9 ο€Ώ 6 π‘₯ + 1 √ π‘₯  π‘₯ 4 π‘₯ 3 l n
  • C 9 ο€Ί √ π‘₯ + 6 π‘₯  + 9 ο€Ώ 2 4 π‘₯ + 1 2 √ π‘₯  π‘₯ 4 π‘₯ 3
  • D 9 ο€Ί √ π‘₯ + 6 π‘₯  9 + 9 ο€Ώ 2 4 π‘₯ + 1 2 √ π‘₯  π‘₯ 4 π‘₯ 3 l n

Q15:

Given 𝑦 = 5 ο€Ί 5 √ π‘₯ + 9 π‘₯  π‘₯ 3 , find d d 𝑦 π‘₯ .

  • A 5 ο€Ώ 2 7 π‘₯ + 5 2 √ π‘₯  + ο€Ί 5 √ π‘₯ + 9 π‘₯  5 π‘₯ 2 3 l n
  • B 5 ο€Ί 5 √ π‘₯ + 9 π‘₯  5 + 5 ο€Ώ 9 π‘₯ + 5 √ π‘₯  π‘₯ 3 π‘₯ 2 l n
  • C 5 ο€Ί 5 √ π‘₯ + 9 π‘₯  + 5 ο€Ώ 2 7 π‘₯ + 5 2 √ π‘₯  π‘₯ 3 π‘₯ 2
  • D 5 ο€Ί 5 √ π‘₯ + 9 π‘₯  5 + 5 ο€Ώ 2 7 π‘₯ + 5 2 √ π‘₯  π‘₯ 3 π‘₯ 2 l n

Q16:

Find d d 𝑦 π‘₯ if 𝑦 = 3 6 s e c 2 π‘₯ .

  • A 7 2 Γ— 3 6 π‘₯ π‘₯ l n t a n s e c s e c 2 π‘₯ 2
  • B 3 6 Γ— 3 6 π‘₯ π‘₯ s e c 2 π‘₯ 2 l n t a n s e c
  • C 3 6 Γ— 2 3 6 π‘₯ π‘₯ s e c 2 π‘₯ l n t a n s e c
  • D 3 6 Γ— 2 3 6 π‘₯ π‘₯ s e c 2 π‘₯ 2 l n t a n s e c